Association Between Changes in Muscle Strength and Risk of Depressive Symptoms Among Chinese Female College Students: A Prospective Cohort Study - Cao, Jianhua; Zhao, Fang; Ren, Zhongyu (Frontiers in Public Health, 2021)
Muscle strength can be a predictor of depressive symptoms among the elderly. We conducted a prospective study aiming to examine the association between change of handgrip strength and the incidence risk of depressive symptoms among Chinese female college students. Handgrip strength was used as a representative indicator of skeletal muscle strength, and a handheld digital smedley dynamometer was applied to measure handgrip strength. We also used the 20-item Zung self-rating depression scale to evaluate depressive status, and a score of ≥50 indicated moderate-to-severe depressive symptoms. During a 1-year follow-up period, the incidence of depressive symptoms is 10.7%. Multivariate logistic regressions analysis revealed that the multivariable-adjusted ORs (95% CI) of depressive symptoms for the categories of handgrip strength change was 1.00 (reference) for group 1, 0.57 (0.28, 1.19) for group 2, 0.41 (0.19, 0.89) for group 3 and 0.33 (0.11, 0.99) for group 4 (p = 0.018). This study indicated that change of handgrip strength level over one-year period is negatively associated with risk of depressive symptoms among Chinese female college students.